Workshop Kiat-Kiat Menjadi Penulis Artikel Jurnal Internasional Dan Membuat Akun Google Schoolar Untuk Mahasiswa - Zulhendri, Zulhendri; Ediputra, Kasman; Sumianto, Sumianto; Hidayat, Adityawarman (Institut Teknologi Pendidikan Indonesia, 2024)
Writing articles that meet international quality requires quite a lot of effort. Mastery of Academic English plays a major role in the ability to manage established journals (Shinta 2, Shinta 1, and indexed by scopus.com/Web of Science). Of course, to be able to write in reputable international journals or manage highly reputable journals, you need special tips from experts in the field of scientific journals. Based on discussions with several lecturers at Pahlawan Tuanku Tambusai University, data was obtained that students need to write journals by creating a Google Schoolar account for students. Therefore, an application program training activity is needed that can solve the above problems. The community service team considers that the problem of becoming an international journal writer cannot be solved using normal methods. They can use substitution methods to make it easier to solve. In this case, the community service team offers an easier way to complete the tips for becoming an international journal article writer and creating a Google Schoolar account for students.